China's approach to international climate policy: Change begins at home - Susanne Dröge; Gudrun Wacker (Stiftung Wissenschaft und Politik (SWP), 2014)
Chinese government officials have repeatedly declared that China - now the world's biggest greenhouse gas emitter - wants to take on more responsibility for climate policy at the international level. Chinese emissions targets were announced in July at the Petersberg Climate Dialogue, but were then withdrawn. China, along with the United States, will play a decisive role in preparations for the Climate Summit of the United Nations Framework Convention on Climate Change (UNFCCC) in Paris in 2015, during which a new agreement is to be launched. At home, China faces the challenge of reducing the tremendous harm done to its population by smog and environmental damage. Ad hoc measures may achieve quick successes, but without major structural changes the emissions trend will not change. This is challenging for Beijing, as can be seen in its wavering over international commitments. China's international involvement depends on: momentum from the U.S.; balancing the interests of developing countries; and the readiness of the EU to press forward on important issues bilaterally rather than internationally. (SWP Comments)
Keywords: 320